Tirzepatide Once Weekly for the Treatment of Obesity - Jastreboff, Ania M.; Aronne, Louis J.; Ahmad, Nadia N.; Wharton, Sean; Connery, Lisa; Alves, Breno; Kiyosue, Arihiro; Zhang, Shuyu; Liu, Bing; Bunck, Mathijs C.; Stefanski, Adam (The New England journal of medicine, 2022)
In this randomized trial, adults with obesity treated with weekly tirzepatide, a glucose-dependent insulinotropic polypeptide and glucagon-like peptide-1 receptor agonist, had major weight loss over 72 weeks.